The 1546 Vilnius Synod of the Eastern Orthodox Church and the Narrative of Szymon Budny on the Conflict between Monk Arsenii of Suprasl and his Archimandrite Sergii Kimbar - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2015)
It is usual to doubt the historicity of the Vilnius Eastern Orthodox Synod of 1546. There are no survived acts nor decisions of the synod which is known primarily from the letter sent earlier the same year by the king Sigismund II Augustus to the Kievan metropolitan Makarii who was urged by the king to call a synod. Nearly 50 years ago, Mieczysław Gębarowicz advanced an ad hoc idea that Symon Budny’s information (published in his edition: Nowy Testament, Łosk, 1574, p. 25–26) concerning a conflict between the Suprasl monk Arsenii and his archimandrite Sergii Kimbar (who was accused of having willfully modified the monastery rite and also edited the text of the Gospels) having been discussed at a synod may be considered a proof of the 1546 Vilnius Synod historicity. In the present article, the author attempts to further elaborate and give reason to this productive idea which has not as yet received proper attention. Moreover, an additional attempt is made to identify one more (besides the Suprasl conflict) and, as it seems, the most important item in the agenda of the 1546 Vilnius Synod.